2023
DOI: 10.1108/mbr-06-2022-0088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of target industry growth on premiums in cross-border acquisitions

Abstract: Purpose In this paper, the knowledge-based view of the firm is applied to theoretically elucidate and empirically examine the influence of target industry growth on premium payments in cross-border acquisitions. This study aims to extend internally driven Mergers and Acquisitions research efforts of acquirers to industry contingencies of targets by analyzing cross-border acquirers located within the group of seven (G7) countries. Design/methodology/approach This study’s investigation covers 209 cross-border … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 123 publications
(197 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the CEO's characteristics, including hubris or excessive self-confidence, explain a significant portion of M&A premiums quantitatively (Brahma et al, 2023). These factors contribute to the final M&A transaction price being determined at a higher price than the preacquisition market value of the target firm, and the difference between this price and the fair value can be interpreted as a premium at the time of the M&A transaction (Bebenroth & Ahmed, 2023). Unfortunately, this premium ultimately negatively affects the interests of acquiring company shareholders (Can & Dizdarlar, 2022).…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the CEO's characteristics, including hubris or excessive self-confidence, explain a significant portion of M&A premiums quantitatively (Brahma et al, 2023). These factors contribute to the final M&A transaction price being determined at a higher price than the preacquisition market value of the target firm, and the difference between this price and the fair value can be interpreted as a premium at the time of the M&A transaction (Bebenroth & Ahmed, 2023). Unfortunately, this premium ultimately negatively affects the interests of acquiring company shareholders (Can & Dizdarlar, 2022).…”
Section: Results Discussionmentioning
confidence: 99%
“…These additional amounts may be higher depending on the competitive environment surrounding the M&A (Just, Honold, & Meckl, 2023). These factors contribute to the final M&A transaction price being determined at a higher price than the pre-acquisition market value of the target firm, and the difference between this price and the fair value can be interpreted as a premium at the time of the M&A transaction (Bebenroth & Ahmed, 2023). Most previous studies have indicated a tendency for excessive premiums to be paid in merger and acquisition transactions, resulting in the overvaluation of the transaction value (Zhang, Zhang, Yu, & Ma, 2023).…”
Section: Mergers and Acquisitions Transaction Pricementioning
confidence: 99%